2021
DOI: 10.1128/msphere.00081-21
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Infection Alters the Viral Composition of Plasma in Men Who Have Sex with Men

Abstract: Altered gut virome and expanded abundance of certain viruses were found in HIV-1-infected individuals. It remains largely unknown how plasma virus composition changes during HIV-1 infection and antiretroviral therapy (ART). We performed viral metagenomic analysis on viral particles enriched from human plasma from 101 men who have sex with men (MSM) with or without HIV-1 infection and whether or not on ART and compared the differences in the plasma virome. An increased plasma viral abundance of main eukaryotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…The infections with HIV-1, HCV and/or HBV may have impaired the immune system, and make the latter unable to control the replication of some resident viruses such as anelloviruses. This is particularly true as some previous studies have consistently found that increased anellovirus load was associated with HIV-1 infections, and the anellovirus load was inversely correlated with CD4 + T cell counts in MSM ( 30 , 56 ).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The infections with HIV-1, HCV and/or HBV may have impaired the immune system, and make the latter unable to control the replication of some resident viruses such as anelloviruses. This is particularly true as some previous studies have consistently found that increased anellovirus load was associated with HIV-1 infections, and the anellovirus load was inversely correlated with CD4 + T cell counts in MSM ( 30 , 56 ).…”
Section: Discussionmentioning
confidence: 75%
“…The detection rate of HPgV was well consistent with its prevalence in these populations ( 42 ). We previously reported significantly negative correlations of HPgV abundance with HIV-1 and anellovirus abundance in men who have sex with men (MSM) ( 30 ), while the correlations were not found in IDUs ( P = 0.53 and 0.76) (Fig. S5).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…It is of note, however, that we observed higher AV DNA concentrations in the blood of HIV-1-infected children and the breast milk of HIV-1-positive women compared to samples derived from HIV-1 negative subjects. It has been reported that individuals infected by HIV-1 tend to have higher levels of AV [ 5 , 7 ] and that there is a positive correlation between the levels of immunosuppression and AV abundance [ 28 ]. The HIV-1 positive children from our dataset were not breastfed, but still contained high levels of AVs in their blood already at 2 months of age.…”
Section: Discussionmentioning
confidence: 99%
“…AVs are widespread in the human population, however, the source and the moment of the first infection are still not clear [ 3 , 4 ]. Of note, higher levels of AV DNA are found in immunocompromised people, for instance, in HIV-1 positive subjects [ 5 , 6 , 7 ]. Since the HIV-1 infected individuals have significantly higher AV DNA prevalence and concentration compared to HIV-1 negative people, the transmission of AVs may be enhanced in these individuals [ 6 ].…”
Section: Introductionmentioning
confidence: 99%